Bridging Ayurveda and Modern Health Systems: Holistic Perspectives on Prevention and Well-Being (Bheshaja: Journal of Central Ayurveda Campus, 2025)
Ayurveda offers a multidimensional approach to health that closely aligns with modern public health objectives. With its roots deeply embedded in preventive care and wellness, Ayurveda addresses not only physical ailments but also mental and social health dimensions. This article critically explores Ayurveda’s relevance in public health, particularly in the context of India and Nepal, where it continues to be a widely practiced healthcare system. Concepts such as Dinacharya, Ratricharya, Ritucharya, Aharavidhi, and Swastavritta underscore lifestyle and seasonal regimens that foster health resilience. This paper examines how Ayurvedic principles can contribute meaningfully to public health by promoting wellness, preventing illness, and managing chronic and lifestyle-related disorders and also discusses challenges in integrating Ayurveda into mainstream public health, and proposes strategic measures to enhance its global applicability. It reaffirms that the foundational objectives of public health and Ayurveda are remarkably similar—preventing disease, promoting longevity, and enhancing quality of life. With the rise of lifestyle disorders, Ayurveda’s preventive strategies and holistic treatments offer an effective alternative to allopathy-centered health models.